1990
DOI: 10.1002/cjce.5450680624
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer coefficients in finned‐coil stirred‐tank systems

Abstract: Steady-state and transient heat transfer coefficients were determined for a finned-coil, stirred-tank system using tlatblade turbine impellers in water. Fin spacing, flowrate, hot water temperature and agitator speed were varied for Re between 20 000 -110 000 for the agitated side.Individual transfer coefficients were calculated from the experimental overall coefficients. The correlation developed for predicting external transfer coefficients in agitated systems with finned-tube coils was tested against transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Aksan et al 13 (six‐blade paddle and water as fluid). Kizilcec et al 14 determined the HTC for a finned‐coil stirred tank (six blade paddle and water). Mohan et al 15 reported a review on heat transfer to Newtonian fluids in stirred tanks for both jacket and coil side heat transfer.…”
Section: Previous Workmentioning
confidence: 99%
“…Aksan et al 13 (six‐blade paddle and water as fluid). Kizilcec et al 14 determined the HTC for a finned‐coil stirred tank (six blade paddle and water). Mohan et al 15 reported a review on heat transfer to Newtonian fluids in stirred tanks for both jacket and coil side heat transfer.…”
Section: Previous Workmentioning
confidence: 99%